Estudantes-cartógrafos : mapas colaborativos, celulares e tecnologias de informação e comunicação na escola - Coelho, Patrícia Silva Leal (2016)
The creation of maps and the act of mapping, for a long time was restricted to a group of persons or institutions. From the spatial turn occurred in the late twentieth century, in addition to technological innovations observed in the early twenty-first century, Cartography gained new features is the content production mode or the way that content is shared. These new possibilities generate crossings and new capabilities. To better understand how to place these new relationships between the development of maps and new technologies of information and communication, it is used as a means of reflection and analysis a school unit, whose students are in the final stage of basic education (high school), a neighborhood located in the city of Serra, of which the Greater Jacaraípe. For this, there was the handling and interaction between technological devices with mapping capability, the ratio of data generation. These data, obtained through digital maps, videos, photos, sketches and more. These possibilities allow better understand what the relationship of individuals to space and the processes generated from these relationships.